KENDALA DAN STRATEGI GURU DALAM MEMOTIVASI ANAK UNTUK BELAJAR DARI RUMAH (BDR) PADA MASA PANDEMI COVID-19 DI PAUD NEGERI PERCONTOHAN KABUPATEN SIJUNJUNG - Vera Wati; Suswati Hendriani; Irman Irman; Yuliana Nelisma (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2022)
The COVID-19 pandemic has changed study practices and habits. Learning that is usually carried out in the education unit then moves to learning from home (BDR). Teachers and students are involved in distance learning which presents a number of challenges ranging from the obstacles experienced in BDR, both obstacles in planning, implementing and assessing learning, as well as requiring teachers to try to motivate children in implementing BDR during this pandemic. This is because changes in learning patterns that are so drastic have the risk of causing a decrease in the quality of learning. Whereas the quality of learning is the key to student learning outcomes. If the quality of learning decreases, the learning outcomes of students also tend to decrease (learning loss). This study aims to describe the obstacles experienced and the teacher's strategies in motivating children to learn from home (BDR) during the Covid-19 pandemic at PAUD Negeri Pilot Sijunjung Regency. This type of research is a qualitative research with a case study design. This research was carried out at the Pilot State PAUD in June and July 2021. The primary data sources or core informants in this study were 6 people, namely the teacher council, additional informants from the principal. The researcher acts as a key instrument, using supporting instruments in the form of interview guidelines and documentation studies. Secondary data in this study were related documents regarding BDR learning during the covid 19 pandemic. Data collection techniques were carried out by interviews and documentation studies, then the data collected was tested for validity using triangulation techniques. Then the data is analyzed using the opinions of Milles and Hubberman through reduction, data presentation and drawing conclusions. The results of the study indicate that the teacher's obstacles in implementing BDR include obstacles in BDR planning, teachers are constrained in determining learning indicators. In the implementation of BDR, the teacher has difficulty in determining activities according to the situation and condition of the child, while in the BDR assessment, the teacher is constrained in assessing aspects of child development because the child's development cannot be monitored by the teacher. The teacher's strategy in motivating children to BDR is to provide BDR activities according to the child's world, namely through games, creating whatshaap groups, delivering interesting learning videos, giving rewards in the form of words of praise and emoticons that add to the passion and enthusiasm of children in implementing BDR.